Volcanic ash and respiratory symptoms in children on the island of Montserrat, British West Indies. Issue 3 (1st March 2003) - Forbes, L; Jarvis, D; Potts, J; Baxter, P J
Abstract : Background: In July 1995 the volcano on the West Indian island of Montserrat erupted after being inactive for several hundred years. Since then, clouds of ash have been released intermittently from the volcano. Some of this ash is <10 μm in diameter and therefore respirable. Concerns were raised that the particles might cause respiratory problems. Aims: To evaluate whether ashfalls had any effect on the respiratory health of children in Montserrat. Methods: A survey of asthma diagnoses, respiratory symptoms, exercise induced bronchoconstriction (EIB), and current and previous exposure to volcanic ash was carried out in schools in Montserrat during February 1998. Results: Questionnaire information was available for nearly 80% of the 443 children on the school rolls. The prevalence of wheeze symptoms in the previous 12 months was 18% in children aged 12 years and under and 16% in children aged 13 years and over. In children aged 12 and under, the prevalence of wheeze was greater in those who had ever been heavily or moderately exposed to volcanic ash compared with the group who had only ever been exposed to low levels (wheeze in last 12 months: odds ratio (OR) 4.30; wheeze ever: OR 3.45). The prevalence of EIB in 8–12 year olds was about four times higher in those who were currently heavily exposed to volcanic ash (OR 3.85) compared to those currently exposed to low levels. Conclusions: Volcanic ash emissions adversely affected the respiratory health of Montserrat children. The findings emphasise the need to limit exposures of children to volcanic ash and ensure the appropriate management of respiratory symptoms.